Synthesis and Applications of Hematite α-Fe2O3 : a Review - Muhajir, Muhamad; Puspitasari, Poppy; Abdul Razak, Jeefferie (Universitas Negeri Malang, 2019)
This article reviewed the hematite α-Fe2O3, which focuses on its material properties, nanostructures, synthesis techniques, and its numerous applications. Researchers prepared the hematite nanostructure using the synthesis methods, such as hydrothermal, and, further, enhanced it by improving the techniques to accommodate the best performance for specific applications and to explore new applications of hematite in humidity sensing.